DBD EVENT MAPPING, STRONG RELATION OF CLIMATE CONDITIONS AND POPULATION MOBILITY NUMBER WITH DBD INCIDENCE - Nandella Larasati; Ririh Yudhastuti (Universitas Airlangga, 2020)
ABSTRACTDengue Hemorrhagic Fever (DHF) is influenced by the environmental factors; climate and population mobility. The DHF incident mapping is conducted to know its distribution and the areas belong to high-risk of DHF. This study aims to know the DHF incident mapping, climate conditions, and population mobility at Putat Jaya in 2015-2017.This study is an observation analysis by using the ecology time series study. There were 110 samples population. This study used a correlation test to know the strength and weakness of climate variable, population mobility number towards the DHF incident. The data used a primary and secondary data. Most cases of DHF incident are found in community areas (RW) where the distance between citizen’s house is narrow. The mapping showed the distribution pattern of DHF in each RW was grouping and spreading. Based on the correlation test, if the rainfall is higher, the DHF incident increases (r = 0,278). If the air temperature is higher, the DHF incident decreases (r = -0.480). If the humidity is higher, the DHF incident increases (r = 0.282). If the duration of solar radiation is higher, the DHF incident decreases (r = -0,150). If the population mobility rate is higher, the DHF incident increases (r = 0,413). There was an environmental factor that support the DHF incident at Putat Jaya. It causes a high-risk exposure to DHF, thus the case was grouping and spreading. In addition, it still need a cooperation between the Health Center and the society to control the DHF incident. Keywords: Mobility Rate, Climate, Larva Density, Mapping